Experimental study on leak flow rate characteristics of high pressure subcooled water through axial and circumferential microcracks of steam generator tubes under high back pressure conditions. (15th September 2020) - Zhang, K.; Shi, Y.G.; You, H.B.; Zhao, X.H.; Tian, W.X.; Su, G.H.; Qiu, S.Z.
Abstract: Leak-before-break analyses on tube microcracks are beneficial for preventing small loss of coolant accident in nuclear power plants. Specially, the tube leakage of steam generator may lead to steam generator tube rupture. Currently, experimental investigations on leak flow rate characteristics of normal temperature water and high pressure subcooled water through axial and circumferential microcracks of steam generator tubes were carried out, respectively. Cold Test results indicate that leak flow rates of circumferential microcracks for 0.13 ≤  W  ≤ 0.16 mm and 3.6 ≤  δ / D h  ≤ 4.4 increase with a decreasing back pressure ( P out ) first and then can be regarded as a constant value for a given working pressure in steam generator tubes ( P in ). Additionally, each of P in has a critical differential pressure between P in and P out (Δ P c ). The ratio of Δ P c to P in is equal to 0.55, which is smaller than 0.64 for axial microcracks. Hot Test results show that leak flow rates decrease significantly with an increasing working fluid temperature ( T f, in ) when T f, in is larger than a certain value due to the flashing of subcooled water near exits of microcracks. Besides, discharge coefficients of high pressure subcooled water through axial and circumferential microcracks under various back pressure conditions decreases with an increasing P in for a given subcooled temperature. In general, new correlations were developed to give excellent predictions for the leak flow rate data of normal temperature water and high pressure subcooled water through axial and circumferential microcracks of steam generator tubes under various back pressure conditions with a maximum deviation of ±6%.